P-T Path of a Variscan Shear Zone recorded on Quartz-Aluminous Shearband Boudins - Rodrigues, Benedito C. (2013)
The work is focused on the P-T path recorded on internal shearband boudin microstructures, developed during simple shear progressive deformation (Malpica-Lamego Ductile Shear Zone – MLDSZ, NW Portugal). In the studied area, MLDSZ is a NW-SE striking Variscan crustal shear zone with a subvertical and west-dipping foliation and a sub-horizontal stretching lineation; it is recorded as a heterogeneous simple shear zone with bulk left-lateral kinematics (Pamplona and Rodrigues, 2011). The deformation zone is marked by a generalized foliation (Sn) defined by Bt+Ms±Sil and a stretching mineral lineation marked by sillimanite fibres. Microstructural analysis, fluid inclusions studies, Raman spectroscopy, crystallographic preferred orientation on quartz grains and fractal geometry based analysis were applied to the boudins.